Uma revisão sobre os estudos de dietas de aves brasileiras - Costa, Caik Firmino (2023)
Food is something necessary to support life and studies on diet are fundamental for understanding the ecology, evolution and conservation of species. In addition, a growing number of works have been demonstrating that anthropic activities can interfere with the availability of food for organisms, putting many of them at risk of extinction. Although several methodologies for the study of diets have been proposed in recent years, a large number of species still lack detailed studies on the food components they consume. For this reason, the objective of this work was to carry out a bibliographic survey of Brazilian bird species that have studied their diets and the methodologies used, with emphasis on endangered species. Of the 1971 bird species that occur in Brazil, 171 had some type of diet study (8.6% of the species). Among the 254 taxa threatened with extinction, only 15 had some type of diet study performed (10.6%). Most studies/species used the fecal sample analysis method (n = 64), followed by stomach analyzes of slaughtered birds (n = 44); direct observations (n ​​= 40); natural regurgitation (n = 9); chemical regurgitation (n = 38); collection of egregopylae (n = 4) and radioactive isotopes (n = 22). This lack of data is worrying, since the number of species worldwide whose populations have been reduced due to direct and indirect effects of the availability of food resources is increasing. Thus, this subject should be further explored in order to obtain more information to assist in the conservation of the species.